Influence of Polite Language and Good Promotion Towards Increasing Sales Volume Goods: A Case Study of Weekly Market Traders at CFD Boulevard, Makassar City, Indonesia - Serang, Serlin; Mandung, Fitriani (Manunggal Halim Jaya, 2025)
This study aims to identify and analyze the influence of polite language and effective promotion on increasing the sales volume of goods among weekly market traders at Car Free Day (CFD) Boulevard, Makassar City. This research adopts a quantitative approach and utilizes a survey method with questionnaires as the primary data collection tool. The data collected were processed using SPSS version 23 to obtain the research findings. The sample consisted of 165 respondents, selected from a total population of 282 weekly traders at CFD Boulevard, Makassar City. The criteria for inclusion were traders who used tents or tarpaulins on the street and had consistently participated in the CFD market for eight consecutive weeks. The sample size was determined using the Slovin formula with a margin of error 0.05. The analytical methods employed in this study included descriptive analysis, validity and reliability tests, classical assumption tests (including multicollinearity and heteroscedasticity tests), and multiple linear regression analysis, all aligned with the study's conceptual framework. The findings revealed that both polite language and effective promotion positively and significantly impact the sales volume of goods among weekly market traders at Car Free Day Boulevard, Makassar City.